Bureaucratic Pathology in Public Services at The Office of the Department of Population and Civil Registration of Supiori District - Rani Maswati (Doctoral Program of Social Science Pasundan University, 2023)
Bureaucratic pathology is the problem that arises in the service at each government agency that has an impact on public services that are less effective and efficient. The purpose of this study was to determine the pathology of bureaucracy in public services at the Supiori Regency Population and Civil Registration Office and the efforts made to minimize pathology bureaucracy so that there are alternatives and solutions in completing services. The method in this research uses a qualitative descriptive approach in analyzing problems that occur in the field that are used by researchers in natural object conditions, where researchers act as key instruments. The results of the study show that the form of bureaucratic pathology found in the Office of the Population and Civil Registration Service in Supiori Regency is still found that service-convoluted convoluted, the delay in completing the printing of the E KTP is due to the unavailability of blanks ; lack of employee discipline when coming to work, negligence of officers in service time management so that there is uncertainty when it will be finished, there are differences in service to the community, especially persons who prioritize relatives or family then efforts are made to minimize bureaucratic pathology with regulations that are appropriate and strict with officers, simplification of procedure services and logical explanations so that people understand the conditions that occur.